An improved 1D diode model for the accurate modeling of parasitics in silicon modulators - Prosopio-Galarza R.R. (2021)
The authors acknowledge funding support from CONCYTEC-FONDECYT within the call E041-01 [contract number 015-2018-FONDECYT/BM]. H.E.H. acknowledges funding support from the Brazilian Agency CNPq under Projects No 465757/2014-6 (INCT FOTONICOM) and No 312714/2019-2 (HEH’s Research Productivity Grant)